The consul vanishes? On using and not using Gregory the Great's Register in early medieval England. - Savill, Benjamin (Early Medieval Europe, 2024)
This article builds upon recent scholarship emphasizing the importance of Gregory the Great's Register as a key text of the Carolingian and post‐Carolingian library, exploring by contrast its peculiarly limited reception in England. It first surveys what little evidence we have for its citation by English ecclesiastics (post‐c.1000, mostly via Wulfstan); it then examines the single text in a pre‐Conquest manuscript usually catalogued as a letter from the Register, showing that this has been reworked as an anonymous admonitio to judges (probably bishops). It concludes by reflecting on the implications of this limited reception for our understanding of the later Anglo‐Saxon church – a community otherwise well‐invested in Gregory's memory.